2000
DOI: 10.1046/j.1365-2141.2000.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic overexpression of membrane‐bound flt3 ligand by T lymphocytes in severe aplastic anaemia

Abstract: Aplastic anaemia (AA) is an immune‐mediated bone marrow failure associated with high serum levels of flt3 ligand (FL). We examined expression of the membrane‐bound isoform of FL in peripheral blood and bone marrow cells from AA patients at diagnosis (n = 16) and after immunosuppressive (IS) treatment (n = 36). Flow cytometry demonstrated strongly increased FL levels on the cell surface of T lymphocytes in AA relative to normal controls (P < 0·0001). T‐cell‐specific expression of membrane‐bound FL was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…It has been previously reported that the presence of activated T cells in the BM may affect the growth and survival characteristics of BM hematopoietic progenitor cells or even the hematopoiesis supporting capacity of BM stromal cells by inducing intricate cell-tocell interactions and proinflammatory cytokine production. 26,[29][30][31][32][33][34][35] In agreement with previous reports, we found increased numbers of activated T cells in PB of our MS patients, 15,[36][37][38] and also increased proportions of activated T cells in patients' BM. Interestingly, the proportion of HLA-DR þ and CD38 þ cells in patient BM CD3 þ cells inversely correlated with the number of CFCs in the BMMC fraction, suggesting that activated T cells may be implicated in the defective clonogenic potential of hematopoietic progenitor cells in MS.…”
Section: Cytokines In Ltbmc Supernatantssupporting
confidence: 81%
See 2 more Smart Citations
“…It has been previously reported that the presence of activated T cells in the BM may affect the growth and survival characteristics of BM hematopoietic progenitor cells or even the hematopoiesis supporting capacity of BM stromal cells by inducing intricate cell-tocell interactions and proinflammatory cytokine production. 26,[29][30][31][32][33][34][35] In agreement with previous reports, we found increased numbers of activated T cells in PB of our MS patients, 15,[36][37][38] and also increased proportions of activated T cells in patients' BM. Interestingly, the proportion of HLA-DR þ and CD38 þ cells in patient BM CD3 þ cells inversely correlated with the number of CFCs in the BMMC fraction, suggesting that activated T cells may be implicated in the defective clonogenic potential of hematopoietic progenitor cells in MS.…”
Section: Cytokines In Ltbmc Supernatantssupporting
confidence: 81%
“…Overproduction of FL by activated T cells has also been reported as a hematopoietic rescue mechanism in response to BM failure in patients with aplastic anemia. 31 On the other hand, the levels of SDF-1, a cytokine operating in the process of homing of CD34 þ hematopoietic progenitors in the BM, did not differ significantly between MS patients and healthy controls, suggesting probably a normal engraftment support of BM stroma in MS patients undergoing ASCT.…”
Section: Cytokines In Ltbmc Supernatantsmentioning
confidence: 99%
See 1 more Smart Citation
“…1996). Similarly, a study by Pfister et al. (2001) reported that membrane bound FL is increased on CD4 + and CD8 + lymphocytes of severe AA patients.…”
Section: Discussionmentioning
confidence: 71%
“…The precise antigenic targets of cytotoxic T cells are unknown, and the effects of T-cell attack on hematopoietic target cells are poorly characterized. Although the expression levels of a few genes, such as FMS-related tyrosine kinase3 ligand (FLT3L) and GATA2, appear to be different in AA patients and healthy donors, [15][16][17] a more general transcriptome pattern of CD34 cells in AA patients has not been described.…”
Section: Introductionmentioning
confidence: 99%